Effect of Ultra-Short Pulse Signals on Information System Survivability - Serkov, A.A. (Радиофизика и радиоастрономия, 2002)
Here, the problems dealt with a survivability simulation of information systems under destabilizing electromagnetic effect have been considered. Proposed was the graph-analytic model of the information system and the electromagnetic surrounding, which presumes its structure evolution by reconfiguring links between its parts. A model complexity evaluation was carried out taking into account a cardinal number and an entropy. Such an evaluation made it possible to allow for a variety of component parts included into the system. The quantitative measure of model complexity has been obtained. It allowed us to evaluate a level of complexity of information systems in the course of their reconfiguration or degradation as well as to develop methods for making the system simpler and at the same time keeping safe their most essential features and characteristics.